EXPECTED VALUE METHOD OF INFORMATION AND LOST OPPORTUNITIES AS A DECISION-MAKING TOOL - Pramono, Setio; Wahyuni, Sri; Wibowo, Agung; Fahrudin; Mulya, Viona Santi (Universitas Ibn Khaldun Bogor, 2023)
The Expected Value of Information and Opportunity Cost methods have become increasingly popular tools in strategic decision-making. In the context of decision-making, comprehensive information is crucial. If the information is incomplete or based on assumptions, decision-makers will struggle to make precise and clear decisions. Therefore, the concept of probability or likelihood needs to be applied to align with future consequences. Decision-making involves challenging aspects, such as responses to competitors and inflation indices that can affect various aspects within an organization. One form of decision-making involves conditions of risk that must be prepared for. In this scenario, two main criteria exist: Expected Value and Opportunity Loss, providing consistent results. This implies that the application of both methods has been utilized to make the best decisions and can enhance the decision-making process in various contexts. In the analysis of the expected value of information, we explore how the collection of additional information can influence the final decision. On the other hand, in the concept of opportunity cost, we measure the cost of alternative decisions not taken. The integration of these two methods offers a comprehensive and holistic perspective on the decision-making process.